2010
DOI: 10.1136/hrt.2010.198325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of initial rhythm, witnessed status and delay to treatment among survivors of out-of-hospital cardiac arrest in Sweden

Abstract: Among survivors of OHCA, a substantial proportion was found in a non-shockable rhythm and this occurred more frequently in women than in men. The proportion of survivors found in a shockable rhythm has not changed markedly over time. Survivors found in a shockable rhythm had a better cerebral performance than survivors found in a non-shockable rhythm. The proportion of survivors who were bystander-witnessed and found in a shockable rhythm and defibrillated early is still remarkably low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…We have recently reported that, among survivors of OHCA, women constituted the minority 29. We now report that female gender is a predictor of improved outcome when found in a shockable rhythm.…”
Section: Discussionmentioning
confidence: 65%
“…We have recently reported that, among survivors of OHCA, women constituted the minority 29. We now report that female gender is a predictor of improved outcome when found in a shockable rhythm.…”
Section: Discussionmentioning
confidence: 65%
“…46,47 Our study also confirms prior reports that despite an advantage earlier in life, overall survival in women is lower than in men. 8,10,[19][20][21][22][23][24] This could be because a majority (59%) of the cardiac arrests occurred between the ages of 65 and 85 years when men have a survival advantage over women. Also, women have fewer key prehospital factors that improve survival (witnessed arrest and shockable rhythms upon EMS arrival).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] However, data on survival to hospital discharge are conflicting. A majority show either no survival advantage 9,[12][13][14][15][16][17][18] or higher survival in men, 8,10,[19][20][21][22][23][24] while others indicate that women fare better. 18,25,26 Studies that report worse survival in women often attribute it to worse prehospital factors.…”
Section: Academic Emergency Medicinementioning
confidence: 99%
“…The mortality rate post admission to hospital after successful resuscitation from OHCA is high 2. While prehospital factors such as age, bystander cardiopulmonary resuscitation and total cardiac arrest time are known to influence outcome,3 several aspects of post-resuscitative care may also influence overall patient survival. In particular, hospital factors such as hospital size and interventional cardiac care capabilities have been found to influence patient outcome in Sweden,4 Japan5 and North America 6–8.…”
mentioning
confidence: 99%